Black feminism between Najwa Ben Shatwan and Toni Morrison - Mahmoud , Eid; Hussain, Kinan (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
No doubt that the critical discourse, has tended, in its latest stage, to link creativity with its cultural components. For that, woman was present significantly in the cultural criticism domain. Here, we are approaching the black woman in the respect of that she is compounded of two main components: The first one is that she is a black skinned, The second: She is a woman, the matter that makes her burden more pressures and burdens. Since we are focusing, in this research, on the feminist issue, we are not going to approach the space that the black woman occupied in the scale of creativity writing, but we are going to approach the space that the black woman occupied in two novels: Zarayeb al-′Abeed by "Najwa Ben Shatwan", and "mercy" by "Toni Morrison". In another words, the comparative lesson inters the circle of the feminist narration according to the subject, not according to the production. Therefore, the research approaches woman as being the other that divers the man (either black or white), and this is subject to the dominant cultural and social prospects of societies.